The Association of Parenting Styles with Premarital Sexual Behavior in Adolescents - Lumolo, Merry Rosdiana; Shintya, Lea Andy (NUTRIX, 2025)
One form of curiosity in adolescents is sexual behavior that can be misused, leading to premarital sexual behavior and resulting in teenage pregnancies, increased maternal and infant mortality rates, economic immaturity, mental development immaturity, and difficulty controlling emotions, ultimately leading to divorce. To prevent sexual behavior, proper parental upbringing is necessary to shape a child's behavior, and it also serves as proof of parental responsibility in the increasingly mature development and growth stages of a child. The purpose of this study is to determine the relationship between parental parenting styles and premarital sexual behavior in adolescents at SMA Negeri 1 Siau Barat. This research uses a quantitative research method and a cross-sectional research design with 130 research samples, employing convenience sampling as the sample collection technique. The research results show that 124 (95.4%) respondents have an authoritarian parenting style, 3 (2.3%) respondents have a permissive parenting style, and 3 (2.3%) respondents have a democratic parenting style. Premarital sexual behavior was found in 129 (99.2%) respondents who exhibited deviant behavior and 1 (0.8%) respondent who did not exhibit deviant behavior. The results of the Kruskal-Wallis statistical test showed a p-value of 0.009 < 0.05, indicating a significant relationship between parental parenting styles and premarital sexual behavior in adolescents at SMA Negeri 1 Siau Barat. Recommendations for future researchers to add other variables such as peers, social media use, and sex education in schools. Salah satu bentuk rasa ingin tahu pada remaja adalah perilaku seksual yang dapat disalahgunakan, mengarah pada perilaku seksual sebelum menikah dan mengakibatkan kehamilan remaja, peningkatan angka kematian ibu dan bayi, ketidakmatangan ekonomi, ketidakmatangan perkembangan mental, dan kesulitan mengendalikan emosi, yang pada akhirnya menyebabkan perceraian. Untuk mencegah perilaku seksual, pendidikan orang tua yang tepat diperlukan untuk membentuk perilaku anak, dan juga berfungsi sebagai bukti tanggung jawab orang tua dalam tahap perkembangan dan pertumbuhan anak yang semakin matang. Tujuan penelitian ini adalah untuk mengetahui hubungan antara gaya pengasuhan orang tua dan perilaku seksual pranikah pada remaja di SMA Negeri 1 Siau Barat. Penelitian ini menggunakan metode penelitian kuantitatif dan desain penelitian cross-sectional dengan 130 sampel penelitian, menggunakan convenience sampling sebagai teknik pengumpulan sampel. Hasil penelitian menunjukkan bahwa 124 (95,4%) responden memiliki gaya pengasuhan otoriter, 3 (2,3%) responden memiliki gaya pengasuhan permisif, dan 3 (2,3%) responden memiliki gaya pengasuhan demokratis. Perilaku seksual sebelum menikah ditemukan pada 129 (99,2%) responden yang menunjukkan perilaku menyimpang dan 1 (0,8%) responden yang tidak menunjukkan perilaku menyimpang. Hasil uji statistik Kruskal-Wallis menunjukkan nilai p sebesar 0,009 < 0,05, yang mengindikasikan adanya hubungan signifikan antara gaya pengasuhan orang tua dan perilaku seksual pranikah pada remaja di SMA Negeri 1 Siau Barat. Rekomendasi bagi peneliti di masa depan untuk menambahkan variabel lain seperti teman sebaya, penggunaan media sosial, dan pendidikan seks di sekolah.